Optimalisasi Dana Operasional TPQ melalui Pengajuan Keanggotaan FKPQ (Studi Kasus di TPQ Al-Mustajab Surabaya) - Andika Cahya Pratama; Wardatul Humairo; Danny Dwi Robbani (Islamic Education Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2026)
This study aims to analyze and propose a solution for optimizing the operational funding of Qur’anic Education Centers (TPQ) through membership application to the Forum for Qur’anic Education Communication (FKPQ). Employing a qualitative approach with a case study design, the research was conducted at TPQ Al-Mustajab Surabaya, a institution experiencing significant challenges in sustaining its financial operations. The findings reveal that the funding system at TPQ Al-Mustajab is not yet optimal. Financial support relies solely on incidental donations from administrators and the community, with no permanent donors, resulting in limited facilities, unstable incentives for educators, and reduced effectiveness in learning activities that require extended instructional time. These conditions highlight the need for a more structured and sustainable funding strategy. Membership in FKPQ is identified as a potential solution, as it offers administrative support, institutional legitimacy, and opportunities for accessing operational assistance. This effort is expected to enhance the welfare of the institution, educators, and students while strengthening the continuity of Qur’anic education at TPQ Al-Mustajab Surabaya.